Biocompatible Glutathione Capped Functionalized Carbon Dots as Nanosensors for the Detection of Silver Nanoparticles in Aqueous Solution and Human Cells as well as Bacterial Cells. Issue 13 (30th August 2016) - Kong, Lingcan; Lu, Keyu; Ling, Xia; Zhu, Pengfei; Liu, Wenwei; Guan, Hongxia; Wang, Chuanxi
Abstract: Functional carbon materials have aroused much attention owing to their applications in cellular imaging and sensing. In this paper, we use a hydrothermal approach to prepare luminescent sodium citrate carbon dots (CDs) using glutathione (GSH) as the surface capping reagent. The effects of feed ratio, reaction temperature and reaction time on the luminescent behavior of CDs are investigated. Subsequently, as‐prepared CDs are characterized by UV‐vis, photoluminescence, X‐ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FTIR) and transmission electron microscope (TEM). The luminescent CDs exhibit good stability in the presence of various ions or photo irradiation. Furthermore, the luminescence of the CDs is reversible upon the pH cycling between pH=4 and 6. In addition, the emission intensity of CDs decreases gradually with increasing the concentration of silver nanoparticles (AgNPs) and a linear relationship between the logarithm of emission intensity and the concentration of AgNPs is observed within the investigated concentration ranging from 0 to 40 μmolL−1. The detection limit is 0.9 μmolL−1 in terms of signal‐to‐noise ratio of 3. More importantly, the sensor can be successfully applied to the detection of AgNPs in real lake water, urine of human, Hep‐2 cells, E. Coli and Salmonella bacteria, which offers a promising platform for environmental and biological sensing applications. Abstract : Water‐soluble and high fluorescence carbon dots were synthesized using glutathione as the stabilizing agent. The resultant carbon dots could be used as nanosensors for the detection of silver nanoparticles. Moreover, the responsive fluorescence CDs have been successfully applied to sensing and imaging in real lake water, Hep‐2 cells, Escherichia coli and Salmonella bacteria.